2009
DOI: 10.1038/hr.2009.4
|View full text |Cite
|
Sign up to set email alerts
|

Renal and extrarenal mechanisms of perinatal programming after intrauterine growth restriction

Abstract: The concept of fetal programming of disease in later life after intrauterine growth restriction (IUGR) has opened a potential new perspective on the treatment and prevention of arterial hypertension. Numerous large studies have recently confirmed the relationship between low birth weight and raised blood pressure. Hyperalimentation after birth appears to add to the risk of higher blood pressure later in life. However, there is still a controversy and clear intervention studies have not yet been possible. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…123 In a larger study of 19-year-olds who were very preterm, stratified by weight for gestational age, birth weight correlated negatively with serum creatinine and albuminuria and positively with GFR. 124 These results are consistent with those of others, but as has been shown in animal studies, pro- Renal dysfunction Increased renal vascular reactivity 1renal artery response to ␤-adrenergic stimuli and sensitivity to adenylyl cyclase in growth-restricted rats 184,186,187 Altered vascular reactivity 2flow-mediated dilation in LBW children 107,[188][189][190] 1uric acid Endothelial dysfunction Impaired vascular structure and capillary density Altered RAS Administration of inhibitors of RAS abrogates later hypertension 4,30,111,177,191 Administration of angiotensin II causes increased hypertensive response Evidence of expression of AT1R and AT2R and ACE activity are divergent at different stages and in different models of programming Overall, programmed suppression of intrarenal RAS during nephrogenesis and postnatal upregulation of AT1R are most consistent Altered sodium handling 2fractional excretion of sodium 22,109,110,174,192 1expression of BSC1 and TSC 1expression of glucocorticoid receptor 1expression of glucocorticoid responsive ␣1 and ␤1 subunits of Na/K-ATPase 1expression of NHE3 1expression of ␤ and ␥ ENaC Increased sympathetic nervous system activity Renal denervation reduced systolic BP and sodium transporter expression 193 Catch-up growth/obesity Higher BP in children who catch up fastest 98,154 Reduced flow-mediated dilation with higher rate of weight gain AT1R, angiotensin subtype 1 receptor; AT2R, angiotensin subtype 2 receptor; BSC1, bumetanide-sensitive co-transporter; ENaC, epithelial sodium channel; NHE3, sodium hydrogen exchanger; RAS, renin-angiotensin system; TSC, thiazide-sensitive co-transporter.…”
Section: Measures Of Renal Functionsupporting
confidence: 80%
“…123 In a larger study of 19-year-olds who were very preterm, stratified by weight for gestational age, birth weight correlated negatively with serum creatinine and albuminuria and positively with GFR. 124 These results are consistent with those of others, but as has been shown in animal studies, pro- Renal dysfunction Increased renal vascular reactivity 1renal artery response to ␤-adrenergic stimuli and sensitivity to adenylyl cyclase in growth-restricted rats 184,186,187 Altered vascular reactivity 2flow-mediated dilation in LBW children 107,[188][189][190] 1uric acid Endothelial dysfunction Impaired vascular structure and capillary density Altered RAS Administration of inhibitors of RAS abrogates later hypertension 4,30,111,177,191 Administration of angiotensin II causes increased hypertensive response Evidence of expression of AT1R and AT2R and ACE activity are divergent at different stages and in different models of programming Overall, programmed suppression of intrarenal RAS during nephrogenesis and postnatal upregulation of AT1R are most consistent Altered sodium handling 2fractional excretion of sodium 22,109,110,174,192 1expression of BSC1 and TSC 1expression of glucocorticoid receptor 1expression of glucocorticoid responsive ␣1 and ␤1 subunits of Na/K-ATPase 1expression of NHE3 1expression of ␤ and ␥ ENaC Increased sympathetic nervous system activity Renal denervation reduced systolic BP and sodium transporter expression 193 Catch-up growth/obesity Higher BP in children who catch up fastest 98,154 Reduced flow-mediated dilation with higher rate of weight gain AT1R, angiotensin subtype 1 receptor; AT2R, angiotensin subtype 2 receptor; BSC1, bumetanide-sensitive co-transporter; ENaC, epithelial sodium channel; NHE3, sodium hydrogen exchanger; RAS, renin-angiotensin system; TSC, thiazide-sensitive co-transporter.…”
Section: Measures Of Renal Functionsupporting
confidence: 80%
“…[2] Fetal growth restriction has been identified as a risk factor for raised BP in later life. [3,4] Studies addressing the relationship of weight gain in infancy to later life BP have shown mixed results. The Helsinki Birth Cohort study showed an inverse association between infant weight gain and later life BP.…”
Section: Introductionmentioning
confidence: 99%
“…However, programmed nephron deficit has also been described in the absence of hypertension [8], which has led to the suggestion that concomitant changes in renal function must occur in order for hypertension to develop [9]. A major candidate is the intrarenal renin-angiotensin system, which displays altered activity in several models of developmental programming [10,11]. However, there are other changes in the kidney that may also contribute to the onset of hypertension, most notable of which is an increase in renal tubular sodium transporter expression.…”
Section: Introductionmentioning
confidence: 97%